Marketing Strategy of the Skul.Id Platform as a Digital Education Ecosystem in Increasing Telkomsel's Youth Market in the Bali Region - Herywanto; Lahindah, Laura (Indonesian Journal of Multidisciplinary Science, 2025)
The digital transformation in the education sector has driven the growth of various online learning platforms, including Skul.id. Despite offering innovative features, the adoption of Skul.id among students in Bali faces multiple challenges, such as low user engagement and competition from similar platforms. This study aims to analyze Skul.id's marketing strategy and its effectiveness in reaching the youth market of Telkomsel SIM card users in Bali. This research employs a qualitative descriptive approach, utilizing data collection techniques such as in-depth interviews, participatory observations, and document analysis. The research informants include Telkomsel's marketing team and Skul.id users, comprising students and educators in various schools across Bali. The findings indicate that Skul.id’s current marketing strategy has yet to fully optimize its potential in attracting students. Despite its integration with Telkomsel services, limitations in digital promotion efforts and a lack of product differentiation remain major obstacles. Additionally, user trust in the platform's effectiveness poses a significant challenge. The study concludes that the Marketing Mix 7P and STP strategy should be optimized by enhancing digital campaigns, strengthening collaborations with educational institutions, and reinforcing brand positioning to improve Skul.id's competitiveness in the digital education market.